ANALISIS IMPLEMENTSI KURIKULUM MERDEKA PADA PEMBELAJARAN IPAS SISWA KELAS IV SD NEGERI 1 SYAMTALIRA BAYU - Diah Septiana; Samsul Bahri; Nur Anwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Independent Curriculum is a new approach in Indonesia's education system emphasizing differentiated learning, the Pancasila Student Profile strengthening project (P5), and the integration of science and social studies into IPAS. This study aims to describe the implementation of the Independent Curriculum in IPAS learning for fourth-grade students at SD Negeri 1 Syamtalira Bayu and to analyze the obstacles faced. This research employed a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. Data analysis used the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. The results indicate that the implementation of the Independent Curriculum in IPAS learning has been carried out well through planning, implementation, and evaluation. However, teachers encountered obstacles such as preparing teaching modules, limited time, and dynamic classroom conditions. Therefore, teachers are required to be more creative in managing IPAS learning to achieve the curriculum objectives.